Sosialisasi Pencegahan Kekerasan Seksual di Lingkungan Kampus - Iriawan, Hermanu; Krismiyati Krismiyati; Sri Handayani; Edyanto Edyanto (Jurnal Nusantara Berbakti, 2024)
Sexual violence in the campus environment is a serious problem that has a far-reaching impact on the mental, physical, and even academic of the victim. This community service aims to provide socialization about sexual violence prevention strategies in the campus environment. The results of the service show that an effective sexual violence prevention strategy includes several main steps, namely; policy implementation, public awareness and education campaigns, conducting training programs, cooperation with external parties and support services for victims. This comprehensive approach is expected to create a safe, supportive, and inclusive campus environment in the campus environment. The implementation of these strategies can also be a reference for other educational institutions in joint efforts to prevent sexual violence in the educational environment.